2022
DOI: 10.1371/journal.pone.0275281
|View full text |Cite
|
Sign up to set email alerts
|

Gaze perception from head and pupil rotations in 2D and 3D: Typical development and the impact of autism spectrum disorder

Abstract: The study of gaze perception has largely focused on a single cue (the eyes) in two-dimensional settings. While this literature suggests that 2D gaze perception is shaped by atypical development, as in Autism Spectrum Disorder (ASD), gaze perception is in reality contextually-sensitive, perceived as an emergent feature conveyed by the rotation of the pupils and head. We examined gaze perception in this integrative context, across development, among children and adolescents developing typically or with ASD with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The most relevant information on the articles studied for this review can be found in Table 2 , where the author, the type of article, the sample, the intervention, the type of scale used, and the results of each work are indicated. There are six study cases [ 10 , 11 , 12 , 13 , 14 , 15 ], two pilot studies [ 16 , 17 ], and one randomised controlled trial (RCT) [ 50 ]. In these papers, the number of subjects included was 186, of which 27 were known to be female.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most relevant information on the articles studied for this review can be found in Table 2 , where the author, the type of article, the sample, the intervention, the type of scale used, and the results of each work are indicated. There are six study cases [ 10 , 11 , 12 , 13 , 14 , 15 ], two pilot studies [ 16 , 17 ], and one randomised controlled trial (RCT) [ 50 ]. In these papers, the number of subjects included was 186, of which 27 were known to be female.…”
Section: Resultsmentioning
confidence: 99%
“…Searches based on the snowball technique were also carried out, reviewing the reference lists of articles already included for review in this work to verify the existence of additional non-emerging articles in databases. The age exclusion criterion was found to be the most relevant, eliminating some potential articles such as [ 7 , 8 , 9 , 17 , 19 , 20 , 23 , 24 , 25 , 28 , 29 , 32 , 35 ], which clearly showed the therapies performed, the robots used, and the relevant results provided.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation